Regimes de exceção e mobilização das mais-valias fundiárias: o caso das operações urbanas consorciadas em Fortaleza – CE. - Albuquerque, Carla Camila Girão (2015)
This work seeks to contribute to the debate about the centrality of Urban Projects of real estate character made possible by the use of urban instrument Operation Urban Syndicated. The hypothesis defended indicates that the instrument, built to the best and most redistributive production of urban space, has been absorbed by the real estate industry, in partnership with the State, for the management and direction of urban structure with a view to mobilizing capital gains land. Regarded as enabler of an exception scheme for urban legislation, it has taken on increasingly strategic centrality in the scope of urban public policies to enable significant private economic gains transforming the urban instrument financial instrument. Despite the abundance of literature and research has produced on the subject of Urban Operations, little has been on the particular context Northeast, especially of Fortaleza, leaving particularly at this point a significant contribution of labor. The survey, systematization and analysis of information about the mobilization of capital gains realized in five cases of OUCS implemented and in progress demonstrates that local land familiar hegemonic logic influence significantly the decisions taken by the government, which still does not reflect a global economic logic itself. Thus, the State, represented at different levels, is arbitrating exception schemes and legitimizing, imposing a form of production of space that focuses on mobilizing capital gains land by private at the expense of meeting the social needs exacerbated by near-zero recovery the added value compared to private gain.